It’s all about Russia : the reception of contemporary Russian literature in Sweden - Carlström, Malin (Taylor and Francis Ltd., 2025)
Based on a corpus of 377 reviews of 72 novels, this article analyzes how contemporary Russian literature is received and represented in Swedish reviews, in relation to both the Russian literary tradition, and to Russia. The results have been divided into three periods, 1994–2002, 2003–2011 and 2012–2020, and are organized around four themes: (1) contemporary Russian literature in Sweden; (2) contemporary Russian literature in general; (3) contemporary Russian literature in relation to the Russian literary tradition; and (4) contemporary Russian literature in relation to Russia. During the first period, the novels reviewed were described as a new post-Soviet literature portraying the shards of communist society. During the second period, there was a focus on social criticism, while at the same time the critics sensed new hope for Russian literature. The final period is seen as a resurgence of Russian literature, although in a new form. Vladimir Sorokin stands out as the central representative of contemporary Russian literature for the entire period analyzed. Furthermore, contemporary Russian literature is seen as increasingly relevant as Russia’s authoritarian tendencies increase. Finally, Russian literature is seen in Sweden as a source of information about Russia, and as literature in which Russia is the main character.